Results of bronchoscopic excision in typical carcinoid tumors of the lung in Turkey - Hilal Boyacı; Mustafa Çörtük; Şule Gül; Elif Tanrıverdi; Mehmet Akif Özgül; Hüseyin Erhan Dinçer; Erdoğan Çetinkaya (Medicinski glasnik, 2017)
Aim: Carcinoid tumors of the lung are the tumors originating from the neuroendocrine cells. Surgical excision remains the gold standard for the treatment. Treatment with interventional bronchoscopic excision has also been reported as an alternative option in typical carcinoid tumors of the lung. The aim of this study was to present results and outcomes in patients who were bronchoscopically treated and followed-up. Methods: Data of 14 patients, who had undergone bronchoscopic excision due to typical carcinoid tumor of the lung between April 2008 and July 2015 were retrospectively evaluated. Bronchoscopic excision procedures were performed under general anesthesia, while control bronchoscopies were carried out with flexible bronchoscopy. Time between the first and last bronchoscopies was accepted as the follow-up duration. Results: A total of 14 patients was evaluated with eight (57.1%) males. Mean age was 43.57±14.07 (23-68) years. The most common symptoms were shortness of breath and coughing. Mean of 5.69±3.35 (2-12) bronchoscopy procedures were performed in the patients during the diagnosis, treatment and follow-up. Mean follow-up duration was 32.0±19.22 months. At the long-term follow-up, two patients developed 50% stenosis and one patient developed granulation tissue in the endobronchial treatment site. None of the patients developed recurrence during the mean 32-month follow-up. Conclusion: Endobronchial treatment is a safe and successful treatment method in well selected typical carcinoid tumor cases that are centrally located, having no radiological suspicion of local or distant metastasis, distally visible but not located on the bronchi with a wide base on bronchoscopy.
Keywords: bronchoscopy; safety; carcinoid tumor; lung neoplasms; neuroendocrine tumors